CORRUPTION IN MEDICAL PRACTICE: WHERE DO WE STAND? - Yousafzai, Abdul Wahab (Journal of Ayub Medical College Abbottabad, 2015)
Corruption in health care sector affects all countries, including theUnited States,ChinaandIndia. Pakistanis no exception. It is preventing people from having access to the quality medical care. Corruption in medical practice include ordering unnecessary investigations, and procedures for kickbacks and commissions; significant absenteeism, which adversely affects patient care; and the conflict of interest within the physician-pharmaceutical nexus, which exploits patients. To overcome corruption there is need to establish a framework for accountability, eliminating the physician-pharmaceutical nexus; and emphasizing medical ethics at the undergraduate and postgraduate levels. It is also important to open a dialogue amongst health care professionals and encourage the establishment of an ethical health care system in Pakistan.